The effect of buffering on pain and duration of local anesthetic in the face: A double-blind, randomized controlled trial. Issue 4 (December 2013) - Afolabi, Oluwatola; Murphy, Amanda; Chung, Bryan; Lalonde, Donald H
Background: The acidity of lidocaine preparations is believed to contribute to the pain of local anesthetic injection. Objective: To investigate the effect of buffering lidocaine on the pain of injection and duration of anesthetic effect. Methods: A double-blind, randomized trial involving 44 healthy volunteers was conducted. The upper lip was injected with a solution of: lidocaine 1% (Xylocaine, AstraZeneca, Canada, Inc) with epinephrine; and lidocaine 1% with epinephrine and 8.4% sodium bicarbonate. Volunteers reported pain of injection and duration of anesthetic effect. Results: Twenty-six participants found the unbuffered solution to be more painful. Fifteen participants found the buffered solution to be more painful; the difference was not statistically significant. Twenty-one volunteers reported duration of anesthetic effect. The buffered solution provided longer anesthetic effect than the unbuffered solution (P=0.004). Conclusion: Although buffering increased the duration of lidocaine's anesthetic effect in this particular model, a decrease in the pain of the injection was not demonstrated, likely due to limitations of the study.